Sleep quality, physical activity and health status among older persons with various levels of cognitive function in elderly institutions in Peninsular Malaysia / Muhammad Azwan Azri - Azri, Muhammad Azwan (2017)
Several studies have been carried out on residents at the older institutions shows that there are various issues in institutions that lead to decline in functional abilities and health status amongst the residents. The main issues are poor sleep quality, low participation in physical activity and deterioration in health status. Literature stressed that poor sleep quality is more frequent amongst older persons who live in institutions. Sleep disturbance, sleep difficulty and lack of quality of sleep will cause deterioration in health status and quality of life. However, information about sleep quality and factors that affect sleep quality amongst older persons in the institutions in Malaysia is insufficient and inconclusive. Therefore, the aim of this study is to identify sleep quality and factors that influence sleep quality amongst older people in institutions in Malaysia. Information obtains will provide a framework for occupational therapy in Malaysia to design effective intervention to ensure sleep quality amongst older people in institutions. This study found that there is poor sleep quality with median 6.00 (3.00-7.00), low participation in physical activity with median 382.50 (0.00-1017.000) and low level of health status amongst older persons in institutions. Bodily pain emerged as the main predictor for sleep quality. Health care professionals should consider improving sleep quality in order to facilitate enhancement in quality of life amongst older people in institutions.